2017
DOI: 10.1016/j.solmat.2017.05.047
|View full text |Cite
|
Sign up to set email alerts
|

A eutectic salt high temperature phase change material: Thermal stability and corrosion of SS316 with respect to thermal cycling

Abstract: Thermal energy storage (TES) is a critical component in a concentrated solar power (CSP) plant since it is able to provide dispatchability and increase the capacity factor of the plant. Recently the Brayton power cycle using supercritical carbon dioxide (s-CO2) has attracted considerable attention as it allows a higher thermal to electric power conversion efficiency compared to the conventional Rankine cycle using subcritical steam. However, no commercial TES has yet been developed for integration with a s-CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In another study, 145 the eutectic salt was found to have better thermal stability in a CO 2 environment below 700°C than in a N 2 environment. 146 BaCO…”
Section: Corrosivity and Stabilitymentioning
confidence: 99%
“…In another study, 145 the eutectic salt was found to have better thermal stability in a CO 2 environment below 700°C than in a N 2 environment. 146 BaCO…”
Section: Corrosivity and Stabilitymentioning
confidence: 99%
“…Those PCMs include pure substances, eutectic mixtures, and composites that undergo either solid‐liquid or solid‐solid phase transitions. In contrast, only few stability studies have been found for PCMs intended to temperature applications above 100°C.…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform cycling tests, some authors used differential scanning calorimetry (DSC), whereas the majority used set‐ups adapted and/or designed on purpose. Those set‐ups included thermostatic chambers, thermal water baths, electric hot plates with temperature control, weathering chambers, ovens with controlled heating, and, in few cases, also with a cooling control . The advantage of using a DSC apparatus for thermal cycling is that phase change temperature ( T ph‐ch ) and calculated enthalpy (Δ H ph‐ch ) are recorded directly for each cycle, so that their evolution can be monitored without interrupting the test or removing the sample.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations